Short-Term Outcomes of Unresurfaced Patellas in Total Knee Arthroplasty - Khatod, Monti; Inacio, Maria C. S.; Bini, Stefano (The Journal of Knee Surgery, 2013)
Selective patellar resurfacing continues in total knee arthroplasty (TKA). We define the demographics of patients selected for this procedure and report their short-term, aseptic revision rate. A community-based Total Joint Replacement Registry (TJRR) comprising 39,000 TKAs with median follow-up of 24.5 months was evaluated. Patients who underwent bicompartmental TKA were younger (p < 0.001), suffered posttraumatic arthrosis (p < 0.001), and receive hybrid fixation (p < 0.001). In multivariate analysis, the unresurfaced patella is an independent risk factor for early revision with a relative increased risk of 2.3 (95% CI, 1.4–3.7). The cumulative survivorship at 6 years for tricompartmental TKA is 98.1 versus 93.6% for bicompartmental knees (p < 0.001). Despite selecting patients with presumably healthier patellofemoral joints for bicompartmental TKA, the unresurfaced patella remains a risk factor for early revision.
Keywords: knee; patella; arthroplasty; outcomes; revision